2011
DOI: 10.1111/j.1751-9004.2010.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence: Implications for Personal, Social, Academic, and Workplace Success

Abstract: This article presents an overview of the ability model of emotional intelligence and includes a discussion about how and why the concept became useful in both educational and workplace settings. We review the four underlying emotional abilities comprising emotional intelligence and the assessment tools that that have been developed to measure the construct. A primary goal is to provide a review of the research describing the correlates of emotional intelligence. We describe what is known about how emotionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
400
0
59

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 602 publications
(479 citation statements)
references
References 61 publications
20
400
0
59
Order By: Relevance
“…Several studies have attempted to provide evidence in favor of the theoretical, four-branch structure. Some researchers have claimed that their studies support a four-factor MSCEIT structure that is consistent with the four-branch model (e.g., Brackett, Rivers, & Salovey, 2011;Day & Carroll, 2004;Mayer et al, 2002Mayer et al, , 2003. Whereas others have doubts concerning the suitability of this factor structure, in most cases, these researchers have used a college student population (Fan, Jackson, Yang, Tang, & Zhang, 2010;Gardner & Qualter, 2011;Gignac, 2005;Palmer et al, 2005;Roberts et al, 2006;Rode et al, 2008;Rossen, Kranzler, & Algina, 2008) and proposed alternative one-, two-, three-, or four-factor models.…”
Section: Factor Structurementioning
confidence: 99%
“…Several studies have attempted to provide evidence in favor of the theoretical, four-branch structure. Some researchers have claimed that their studies support a four-factor MSCEIT structure that is consistent with the four-branch model (e.g., Brackett, Rivers, & Salovey, 2011;Day & Carroll, 2004;Mayer et al, 2002Mayer et al, , 2003. Whereas others have doubts concerning the suitability of this factor structure, in most cases, these researchers have used a college student population (Fan, Jackson, Yang, Tang, & Zhang, 2010;Gardner & Qualter, 2011;Gignac, 2005;Palmer et al, 2005;Roberts et al, 2006;Rode et al, 2008;Rossen, Kranzler, & Algina, 2008) and proposed alternative one-, two-, three-, or four-factor models.…”
Section: Factor Structurementioning
confidence: 99%
“…In this study, we build on the original concept of EI to explore a variety of social and emotional competencies that become explicit and important within the work environment (Boyatsis & Ratti, 2009;Boyatsis, Stubbs, & Taylor, 2002). These social and emotional competencies are interrelated and form the four core clusters of 1) self-awareness, 2) self-management, 3) relationship management, and 4) social awareness (Brackett, Rivers, & Salovey, 2011;Goleman, 1996;Salovey & Mayer, 1990;Zins & Elias, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…During the past twenty years, the study of emotional intelligence (EI) has experienced great growth both in terms of the number of empirical research studies as well as in the development of its theoretical base (Brackett, Rivers, & Salovey, 2011;Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, 2011;Salovey & Mayer, 1990;Mayer & Salovey, 1997;Weissberg & Durlak, 2005). EI, according to the ability model (Salovey & Mayer, 1990), "involves the ability to monitor one's own and others' emotions, to discriminate among them, and to use the information to guide one 's thinking and actions" (p. 189).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research revealed sex differences in the mean level of emotional abilities and structure of correlations between emotional abilities and social outcomes (Brackett, Mayer & Warner, 2004;Brackett et al, 2011). Visser, Bay, Cook & Myburgh (2010) demonstrated that emotional intelligence has a stronger regulatory role for men.…”
Section: Sex Differencesmentioning
confidence: 99%
“…Emotion understanding is also related to a well-developed emotional dictionary and large knowledge about transitions of emotions in social situations (Brackett, Rivers & Salovey, 2011;Matczak & Piekarska, 2011). The ability to understand emotion could be treated as a component of socio-cognitive comprehension, underlying an insight into the perspective of others and enabling to decode the emotions, goals, desires and intentions of others (de Rosnay & Highes, 2006).…”
Section: Emotion Understandingmentioning
confidence: 99%